FEATURES OF FINANCIAL RESOURCE MANAGEMENT OF TERRITORIAL COMMUNITIES UNDER THE CONDITIONS OF MARITAL STATE IN UKRAINE - Shcherban , O. Ya.; Malik , L. O.; Senyshyn , S. Ye. (The actual problems of regional economy development, 2024)
The purpose of the article is to study the peculiarities of managing the financial resources of territorial communities in the conditions of martial law in Ukraine. This article examines the management of financial resources of territorial communities. It is substantiated that one of the key problems faced by the United Territorial Communities (UTCs) is to ensure the proper performance of their duties. This includes the ability to effectively form a budget, accumulate sufficient financial resources to cover urgent social needs of citizens, in accordance with the principle of subsidiarity, and implement strategies for their economic and technological development. The key sources of funding to support the development of territorial communities in Ukraine against the background of decentralization processes are outlined. The importance of financial support in the process of development of local communities is emphasized. The management of financial resources of territorial communities in Ukraine acquires special relevance in the current conditions of wartime. Therefore, finding effective ways of financing territorial communities for their development, managing local budgets becomes a relevant aspect of scientific research. Successful management of this process involves using the unique capabilities of each territory, attracting various sources of financing, accumulating and effectively distributing resources, creating favorable conditions for the implementation of economic initiatives and local social programs.The main sources of funding for the development of local communities include revenues from local budgets, financial support from the state for local self-government, as well as the attraction of additional financial resources by local authorities through the use of the development potential of the territory. The dynamics and structure of revenues of local budgets, as well as their share in the consolidated budget of the country in recent years, were analyzed. The factors affecting financial management in united territorial communities are highlighted, and the positive influence of community unification on local financial management is emphasized. Justifying the peculiarities of managing financial resources of territorial communities in the conditions of war in Ukraine. Attention is focused on the fact that it is communities who take responsibility for financing a large number of powers, both delegated and their own, which have not yet been clearly defined in the Budget Code. These duties form the basis for local budgets, as they form the foundation for the stability of local finances.